Respuesta :

Answer:

3k2-13k-56

Final result :

(k - 7) • (3k + 8)

Step by step solution :

Step 1 :

Equation at the end of step 1 :

(3k2 - 13k) - 56

Step 2 :

Trying to factor by splitting the middle term

2.1 Factoring 3k2-13k-56

The first term is, 3k2 its coefficient is 3 .

The middle term is, -13k its coefficient is -13 .

The last term, "the constant", is -56

Step-1 : Multiply the coefficient of the first term by the constant 3 • -56 = -168

Step-2 : Find two factors of -168 whose sum equals the coefficient of the middle term, which is -13 .

-168 + 1 = -167

-84 + 2 = -82

-56 + 3 = -53

-42 + 4 = -38

-28 + 6 = -22

-24 + 7 = -17

-21 + 8 = -13 That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -21 and 8

3k2 - 21k + 8k - 56

Step-4 : Add up the first 2 terms, pulling out like factors :

3k • (k-7)

Add up the last 2 terms, pulling out common factors :

8 • (k-7)

Step-5 : Add up the four terms of step 4 :

(3k+8) • (k-7)

Which is the desired factorization

Final result :

(k - 7) • (3k + 8)